A leitura e a biblioteca pública compreendidas pelo Sistema Nacional de Bibliotecas Públicas: uma análise crítica - Fabíola Ribeiro Farias (2013)
This research work identifies and analyses, using two categories, reading and public library, the conception and the social function of public library in two documents from the National System of Public Libraries, a federal institution connected to the Ministry of Culture, legally responsible for orienting the action of the municipal public libraries in the country. The critical reading of the documents Biblioteca pública: princípios e diretrizes (Fundação Biblioteca Nacional, 2000) and Um olhar diferenciado sobre a biblioteca pública: impactos da gestão inovadora (Fundação Biblioteca Nacional, 2009) reveals that they present a superficial understanding of the subject with propositions, orientations and recommendations to the workers of the Brazilian public libraries that lack an appropriate conceptual reflexion. The approach dominant in the documents do not grant a privilege to the intellectual education of the population through the access to knowledge produced and registered in writing, and contributes to the reproduction of social injustice in the country.